Neanderthal subsistence at Chez-Pinaud Jonzac (Charente-Maritime, France): A kill site dominated by reindeer remains, but with a horse-laden diet? - Rendu, William; Renou, Sylvain; Koliasnikova, Anastasiia; Baumann, Malvina; Plisson, Hugues; Discamps, Emmanuel; Soulier, Marie-Cécile; Gicqueau, Arthur; Augoyard, Mathilde; Bocquel, Manon; Guerin, Guillaume; Shnaider, Svetlana; et al. (Frontiers in Ecology and Evolution, 2023)
During the MIS 4 in Southwestern France, Quina Neanderthal from the north of the Aquitaine were characterized by a hunting specialization on the reindeer and the lack of diversity in their diet. They developed task specific locations dedicated to the capture, the butchery and the consumption of reindeer and the whole society seems, in this region, to be dependent of this food resource. In this context, the site of Chez-Pinaud at Jonzac (France) occupies a specific place. Firstly interpreted as a Reindeer kill and butchery site the recent recovery of the site underlines the importance of the large ungulate (Horse and Bison) to the faunal spectrum (30%of the NISP). Considering the quantity of meat and grease that these species can provide to hunters, the new zooarchaeological analyses suggest that at least the horse might have played a major role in the diet of the Neanderthal population. Since Jonzac is one of the largest sites for this period, these results relativize the importance of the reindeer specialization of the Quina population and their lake of diversity in their diet.